Please help with substitution!
![Please help with substitution class=](https://us-static.z-dn.net/files/da7/3e1a92b08630377d53566e09e4cb98ae.jpg)
2. If [tex]y=2x+11[/tex], then in the second equation we'd get
[tex]y+x=5\implies(2x+11)+x=5\implies3x+11=5\implies3x=-6\implies x=-2[/tex]
Then we get [tex]y=2(-2)+11=7[/tex].
3. If [tex]-5x+y=-1[/tex], then [tex]y=5x-1[/tex], and substituting this into the second equation gives
[tex]y-4x=-3\implies(5x-1)-4x=-3\implies x-1=-3\implies x=-2[/tex]
which gives
[tex]y=5(-2)-1=-11[/tex]